Economic Activity of the Population by Age in the European Union Countries - Ewa Pośpiech; Adrianna Mastalerz-Kodzis (Journal of Advanced Research in Social Sciences, 2020)
The employment level research is an important element of economic analyses supporting the conduct of efficient regional or country policy. Many factors influence the level of this phenomenon, these are demographic, social and economic factors. The employment level can be considered in various categories and the demographic changes encourage to carry out employment analyses by age. Therefore, the subject of the analysis was employment (employment rate) of the European Union countries broken down by age. The main purpose of the article was to show similarities and differences in the level and structure of employment occurring in the European Union countries, and besides, examining the existence of spatial patterns in the period under investigation. To achieve this goal, selected quantitative tools were used, including classic and positional measures of central tendency, indicators of dynamics (average change rate) and measures of interdependence between variables (Pearson’s correlation coefficient). In addition, selected spatial autocorrelation measures (global and local Moran’s statistic) were used to identify spatial dependences. Data for analyses were taken from the Eurostat database. The results of the research showed the changing employment structure (by age) in the European Union countries and showed the existence of certain spatial dependences, especially in the oldest group of employed persons.